(8 1/6 - 5/18 ) ÷14/27 - (10 7/8 ÷3/4×2/3+5 3/7÷6 1/3)×3/17=

(8 1/6 - 5/18 ) ÷14/27 - (10 7/8 ÷3/4×2/3+5 3/7÷6 1/3)×3/17=
Гость
Ответ(ы) на вопрос:
Гость
Не знаю даже. Люди, кто решил? Можете проверить =)
Гость
(8 1/6 - 5/18) : 14/27 - (10 7/8 : 3/4 × 2/3 + 5 3/7 : 6 1/3) × 3/17 = 12 2/7 1) 8 1/6 - 5/18 = 7 1/3 2) 10 7/8 : 3/4 = 14 1/2 3) 14 1/2 × 2/3 = 9 2/3 4) 5 3/7 : 6 1/3 = 6/7 5) 9 2/3 + 6/7 = 10 11/21 6) 7 1/3 : 14/27 = 14 1/7 7) 10 11/21 × 3/17 = 1 6/7 8) 14 1/7 - 1 6/7 = 12 2/7
Не нашли ответ?
Ответить на вопрос
Похожие вопросы